INNOVATION IN TEACHING WRITING POETRY USING THE TALKING STICK MODEL - Siti Lamusiah; Humaira; Niswatun Hasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The significance of poetry learning using the Talking Stick innovation lies in its ability to help students develop essential language and literacy skills. Through the activities of reading and writing poetry, students can master language in various forms, develop personal expression, and create meaning. The aim of this study is to assess the extent to which the Talking Stick model can enhance students' creativity in writing poetry and to identify various aspects of creativity that emerge during the poetry writing learning process with the Talking Stick model. This research was conducted at SD 2 Aisyiyah Kota Mataram, involving 16 students as research subjects. The method used is Classroom Action Research (CAR), with qualitative and quantitative descriptive data analysis. The results of the study showed an increase in the students' Minimum Competency Criteria (KKM) scores from cycle I to cycle II. In cycle I, the average KKM score was 72 without using the Talking Stick model in poetry writing learning. However, in cycle II, after implementing the Talking Stick model in poetry writing learning, the average KKM score increased to 76. This indicates that the Talking Stick model has proven effective in enhancing student engagement and participation, and can improve creativity and learning outcomes.